Activation of Indian Hedgehog Promotes Chondrocyte Hypertrophy and Upregulation of MMP-13 in Human Osteoarthritic Cartilage - Wei, Fangyuan (2012)
OBJECTIVE: The objectives of this study were to 1) determine the correlation between osteoarthritis (OA) and Ihh expression, and 2) establish the effects of Ihh on expression of markers of chondrocyte hypertrophy and MMP-13 in human OA cartilage. DESIGN: OA cartilage and synovial fluid samples were obtained during total knee arthroplasty. Normal cartilage samples were obtained from intra-articular tumor resections, and normal synovial fluid samples were obtained from healthy volunteers and the contralateral uninjured knee of patients undergoing anterior cruciate ligament reconstruction. OA was graded using the Mankin score. Expression of Ihh in synovial fluid was determined by western blot. Ihh, type X collagen and MMP-13 mRNA were determined by real time PCR. Protein expression of type X collagen and MMP-13 in cartilage samples were analyzed with immunohistochemistry. Chondrocyte size was measured using image analysis. RESULTS: Ihh expression was increased 2.6 fold in OA cartilage and 37% in OA synovial fluid when compared to normal control samples. Increased expression of Ihh was associated with the severity of OA and expression of markers of chondrocyte hypertrophy: type X collagen and MMP-13, and chondocyte size. Chondrocytes were more spherical with increasing severity of OA. There was a significant correlation between Mankin score and cell size (r(2)= 0.80) and Ihh intensity (r(2) = 0.89). Exogenous Ihh induced a 6.8 fold increase of type X collagen and 2.8 fold increase of MMP-13 mRNA expression in cultured chondrocytes. Conversely, knockdown of Ihh by siRNA and Hh inhibitor Cyclopamine had the opposite effect. CONCLUSIONS: Ihh expression correlates with OA progression and changes in chondrocyte morphology and gene expression consistent with chondrocyte hypertrophy and cartilage degradation seen in OA cartilage. Thus, Ihh may be a potential therapeutic target to prevent OA progression.